2011 Design, Automation &Amp; Test in Europe 2011
DOI: 10.1109/date.2011.5763279
|View full text |Cite
|
Sign up to set email alerts
|

Optimized model checking of multiple properties

Abstract: This paper addresses the problem of model checking multiple properties on the same circuit/system. Although this is a typical scenario in several industrial verification frameworks, most model checkers currently handle single properties, verifying multiple properties one at a time. Possible correlations and shared sub-problems, that could be considered while checking different properties, are typically ignored, either for the sake of simplicity or for Cone-Of-Influence minimization. In this paper we describe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Isolation reduces the SAT formula by dismissing attackers that are outside the COI of the requirement to be verified. Isolation works similarly to COI reduction (see [13,15,7,18,14]), and it transforms Equation 4 into…”
Section: Isolation and Monotonicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation reduces the SAT formula by dismissing attackers that are outside the COI of the requirement to be verified. Isolation works similarly to COI reduction (see [13,15,7,18,14]), and it transforms Equation 4 into…”
Section: Isolation and Monotonicitymentioning
confidence: 99%
“…The works by Cabodi, Camurati and Quer [15], Cabodi et. al [13], and Cabodi and Nocco [14] present several useful techniques that can be used to improve the performance of model checking when verifying multiple properties, including COI reduction and property clustering. We also mention the work by Goldberg et al [20] where they consider the problem of efficiently checking a set of safety properties P 1 to P k by individually checking each property while assuming that all other properties are valid.…”
Section: Related Workmentioning
confidence: 99%
“…The work most similar to ours is a property-clustering procedure based on COI similarity [7,8]. While a similar goal, their solution requires a quadratic number of comparisons between properties, rendering it prohibitively expensive on large testbenches.…”
Section: A Related Workmentioning
confidence: 99%
“…Despite the prevalence of multi-property testbenches, little research has addressed the problem of optimal grouping or clustering of properties into high-affinity groups. Selective past work [7,8] has experimentally demonstrated that ideal grouping may save substantial verification resource. However, no scalable online property grouping procedure has been provided; this potential was illustrated as a proof-of-concept using computationally-prohibitive offline grouping algorithms with undisclosed runtime.…”
Section: Introductionmentioning
confidence: 99%
“…. , P k into smaller clusters of properties [8], which is beyond the scope of this paper. To make joint verification more competitive, in Subsections 9-B and 9-C, we picked sixteen designs (eight designs per subsection) that have less than a thousand properties.…”
Section: Ja-verification Versus Joint Verificationmentioning
confidence: 99%